The Perlocutionary Acts in the Adam Project Movie: Pragmatics Study - Rudy Setiadi; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This researh aims to analyze what is the context of situation that influnces perlocutionary act and grouping them as what type perlocutionary act that found in the Adam Project movie. The method used in this research was a qualitative method. The data used were taken in this research is from the dialogues in The Adam Project movie. The result demonstrated that after analyzed the context of situation that influences perlocutionary act, there are 6 data that contains 3 types of perlocutionary act that found in The Adam Project movie. Furthermore, most of types perlocutionary that found in The Adam Project movie are persuading (50%), then convincing (16,67%) scaring (16,67%) and insulting (16,66%).